2018
DOI: 10.1021/jacs.8b08286
|View full text |Cite
|
Sign up to set email alerts
|

A Room-Temperature Hybrid Lead Iodide Perovskite Ferroelectric

Abstract: Organic-inorganic hybrid perovskite, [CHNH]PbI, holds a great potential for next-generation solar devices. However, whether the ferroelectricity exists in [CHNH]PbI and results in the ultrahigh performance is not at present clear. Beyond that, no hybrid lead iodide perovskite ferroelectric has yet been found. Here, using precise molecular modifications, we successfully designed a room-temperature hybrid perovskite ferroelectric, [(CH)NCHI]PbI. Because of the high-symmetry and nearly spherical shape of [(CH)N] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 22 publications
(11 reference statements)
5
141
0
Order By: Relevance
“…We noted that a mono‐fluorinated molecule is geometrically very similar to its parent molecule, since the substitution of H by an F atom is one of the commonly employed monovalent isosteric replacements . In this way, the fluorinated compounds tend to have similar crystal structures to the hydrogen analogs, and maintain the possibility of orientational disorder as well as phase transitions . And meanwhile, it is through this incorporation of the most electronegative species that not only the barrier of rotation but also the strength of dipole moment of the organic molecules get raised, pointing out an obvious route to enhance the T c and P s .…”
Section: Methodsmentioning
confidence: 99%
“…We noted that a mono‐fluorinated molecule is geometrically very similar to its parent molecule, since the substitution of H by an F atom is one of the commonly employed monovalent isosteric replacements . In this way, the fluorinated compounds tend to have similar crystal structures to the hydrogen analogs, and maintain the possibility of orientational disorder as well as phase transitions . And meanwhile, it is through this incorporation of the most electronegative species that not only the barrier of rotation but also the strength of dipole moment of the organic molecules get raised, pointing out an obvious route to enhance the T c and P s .…”
Section: Methodsmentioning
confidence: 99%
“…But unfortunately, the halogen substituted OHPs ([(CH 3 ) 3 NCH 2 X][Ni(NO 2 ) 3 ], X=F, Cl, Br, I) crystallize in the centrosymmetric space groups (Supporting Information, Table S1). Considering that halogen bonding and hydrogen bonding have a substantial role in generating ferroelectric ordering, [(CH 3 ) 4 N] + was substituted with a hydroxy group so as to act as hydrogen‐bond donors when nitrite groups are the acceptors. However, the resulting OHPs with the orthorhombic centrosymmetric space group Pnma persist the non‐ferroelectric feature (Supporting Information, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…In optical absorption and emission capability tests, TMCM‐MnCl 3 showed six absorption peaks in its spectrum that correspond to the electronic transitions between the ground and the excited states of the Mn 2 + ion, and the wavelength of the emitted light is ≈640 nm . Molecules of TMBM‐MnBr 3 , TMCM‐CdBr 3 and TMIM‐PbI 3 also have similar structures to TMCM‐MnCl 3 and have phase transition temperatures of 415, 346, and 312 K, respectively . Another 1D HOP ferroelectric was synthesized in 2015 by Liao et al They reported a hybrid organo‐plumbate, (benzylammonium) 2 PbCl 4 , which behaves like a semiconductor material.…”
Section: Various Approaches To Construct Hop Spin‐related Optoelectromentioning
confidence: 99%